Comparative analysis of algorithms for solving Sudoku - Wnuk, Emil; Łukasik, Edyta (Journal of Computer Sciences Institute, 2016)
The article presents a comparative analysis of selected algorithms for solving Sudoku. Puzzles of different sizes and having different levels of difficulty are compared. The impact of these factors on the duration of the algorithms is examined. For the study, a special application that contains all the necessary algorithms has been created.